2016
DOI: 10.1139/cjas-2015-0106
|View full text |Cite
|
Sign up to set email alerts
|

Blood haemogram in Ovis aries and Capra hyrcus: effect of storage time

Abstract: The aim of the present study was to assess the effect of storage time at +4°C on haematological profile in goat (n = 25) and sheep (n = 25). After collection, blood samples were immediately analyzed and then divided into four aliquots that were stored at 4°C and tested at 24 h (T1), 48 h (T2), 72 h (T3), and 1 wk (T4), respectively. One-way repeated-measures analysis of variance (ANOVA) was used to determine statistically significant effect of storage conditions both in goats and in sheep. Our results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Blood smear evaluation is also useful for evaluating other preanalytic artifactual changes, as time and temperature can also affect other cell lines . Numerous reports document time‐ and temperature‐dependent changes in RBCs, WBCs, and PLTs, and automated and manual CBC indices in cattle, lab animals, dogs, sheep, goats, horses, turkeys, and harp seals . However, surprisingly, in Xenopus tropicalis , using the Natt‐Herrick solution, cellular integrity was maintained for 2 years post collection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood smear evaluation is also useful for evaluating other preanalytic artifactual changes, as time and temperature can also affect other cell lines . Numerous reports document time‐ and temperature‐dependent changes in RBCs, WBCs, and PLTs, and automated and manual CBC indices in cattle, lab animals, dogs, sheep, goats, horses, turkeys, and harp seals . However, surprisingly, in Xenopus tropicalis , using the Natt‐Herrick solution, cellular integrity was maintained for 2 years post collection …”
Section: Discussionmentioning
confidence: 99%
“…Evaluation and, therefore, interpretation of CBC findings can be limited by certain preanalytical factors. For example, prolonged storage could cause artifactual increases in hematocrit, MCV, and MPV, and decreases in the MCHC and PLT variables . Additionally, in 1984, Gossett and Carakostas showed that prolonged storage of blood in EDTA could cause the development of cytoplasmic vacuoles in neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…Haematological parameters are generally used to monitor and evaluate the health of small ruminants (Fazio et al, 2016). Due to the economic importance of goats, a lot of information is available on their haematology (Tibbo et al, 2004;Zumbo et al, 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…Clotted blood samples were centrifuged2 h after sampling or left at 4°C or 20°C for time intervals of 6h, 12h, 24h, 48h and 72h to simulate potential storage conditions and durations of porcine blood samples before reaching the laboratory. In general, few reports describe effects of temperature and storage duration on biochemical analytes in clotted blood of farm animal species, 11,[15][16][17]25 a couple of these include pigs. [15][16][17] Dissimilarities in e.g.…”
Section: Gamma-glutamyl Transferase (Ggt) and Glutamate Dehydrogenasementioning
confidence: 99%